2021
DOI: 10.1002/jid.3551
|View full text |Cite
|
Sign up to set email alerts
|

The density of microfinance institutions and multiple borrowing in Ghana: Are rural borrowers vulnerable?

Abstract: This primal study investigates the extent of multiple borrowing in Ghana and explores the relationship between the density of microfinance institutions (MFIs) and multiple borrowing. Further analyses examine the susceptibility of rural borrowers, and the influence of individual MFI categories. The incidence of multiple borrowing in Ghana is 35%. Although an increase in MFI density is less likely to engender multiple borrowing, rural clients have a propensity to overlap and are also sensitive to different insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Concentrated market competition and borrowing from multiple lenders are often blamed for over-indebtedness crises in lower-income credit market (Fu, 2020). Ewusie et al (2021) show the positive link between the density of MFIs and multiple borrowing in rural areas in Ghana. Chichaibelu and Waibel (2017) also point out that one of the reasons for rising household debt is the ease of borrowing simultaneously from a growing number of lending institutions.…”
Section: Related Literaturementioning
confidence: 83%
See 1 more Smart Citation
“…Concentrated market competition and borrowing from multiple lenders are often blamed for over-indebtedness crises in lower-income credit market (Fu, 2020). Ewusie et al (2021) show the positive link between the density of MFIs and multiple borrowing in rural areas in Ghana. Chichaibelu and Waibel (2017) also point out that one of the reasons for rising household debt is the ease of borrowing simultaneously from a growing number of lending institutions.…”
Section: Related Literaturementioning
confidence: 83%
“…Ewusie et al. (2021) show the positive link between the density of MFIs and multiple borrowing in rural areas in Ghana. Chichaibelu and Waibel (2017) also point out that one of the reasons for rising household debt is the ease of borrowing simultaneously from a growing number of lending institutions.…”
Section: Related Literaturementioning
confidence: 99%
“…Microfinance institutions are noted globally for their leading role in supporting small and medium enterprises (SMEs) to gain ground and conduct business by providing them with needed financial resources to grow, manage and sustain their businesses. They also contribute to reducing poverty, empowering individuals (Ewusie et al, 2021), especially women (Addai, 2017), and SMEs financially, and improving living standards, an element of the Sustainable Development Goal thus, reducing poverty. Batinge and Jenkins (2021) identified that aside from microfinance institutions (MFI) offering financial assistance, MFI also offer services to women which include training on financial management, skill development and other social services in order to help enhance the welfare of the women.…”
Section: Microfinancementioning
confidence: 99%
“…In Ghana, Ewusie et al, (2021) note that a census of MFI project their number to be approximately 3000 while Alimo (2015) also posits that by categorization, 92% of companies in the country, are SMEs. Thus, micro-credit from MFI is a unique development intervention for small enterprises and also a source of economic relief to the poor.…”
Section: Microfinancementioning
confidence: 99%
See 1 more Smart Citation